Authoritarian Parenting in Early Young Children Life History Study Three Muslim Parents in Yogyakarta - Hastuti, Dwi; Miftah, Muhammad (QUALITY, 2023)
Parenting is very influential in the development of a child. Appropriate parenting will have a positive impact on the growth and development of children both physically and psychologically. This research is motivated by facts in the field based on pre-observations that parents' parenting patterns tend to be authoritarian in early childhood . There were 3 parents met. Authoritarian parenting patterns are found when parents teach in terms of religious education, authoritarianism occured when they teach religious practice. This study aims to determine the factors behind the occurrence of parental authoritarian behavior. This research is a qualitative research with a life history approach that explores individual experiences and knowledge. The ecological theory of Urie Brofenbrenner, the theory of children's education in Islam according to Al-Ghazali, is used as an analytical tool. Based on these 2 theories, the tendency for authoritarian parenting is motivated by previous parenting experiences, and the environment (school and community). The findings and results of the research prove that 3 Muslim parents in the life history study have implemented authoritarian parenting styles for their children in the form of verbal violence (in the form of yelling and labeling children), limiting children from asking questions, rigid rules made unilaterally by parents, communication that tends to be one way and parents' impatience when accompanying children reciting and memorizing which leads to parental anger. Various factors behind the emergence of authoritarian parenting include, (1) parenting patterns obtained from previous parents (2) inappropriate methods of instilling religion (3) demands of schools based on religion, (4) competition between parents. Pola Asuh Otoriter pada Anak Usia Dini Kajian Sejarah Hidup Tiga Orang Tua Muslim di Yogyakarta. Pengasuhan adalah hal yang sangat berpengaruh pada perkembangan seorang anak. Pengasuhan yang tepat akan memberikan dampak yang positif bagi tumbuh kembang anak baik secara fisik maupun psikis. Penelitian ini dilatarbelakangi fakta di lapangan berdasar pra-observasi masih ditemukan pola pengasuhan orang tua yang cenderung otoriter pada anak usia dini. Orang tua yang ditemui berjumlah 3 orang. Pola pengasuhan otoriter ditemui saat orang tua mengajarkan dalam hal pendidikan agama, yaitu saat anak belajar sholat, mengaji dan hafalan. Penelitian ini bertujuan untuk mengetahui faktor yang melatarbelakangi terjadinya perilaku otoriter orang tua. Penelitian ini merupakan penelitian kualitatif dengan pendekatan life history yang mengeksplorasi pengalaman dan pengetahuan individu. Teori ekologi Urie Brofenbrenner, teori pendidikan anak dalam Islam menurut Al-Ghazali dpakai sebagai pisau analisa. Berdasar 2 teori tersebut, kecenderungan pengasuhan otoriter dilatarbelakangi oleh pengalaman pengasuhan yang diperoleh sebelumnya, dan lingkungan (sekolah maupun masyarakat). Temuan dan hasil penelitian membuktikan bahwa 3 orang tua Muslim dalam kajian life history tersebut telah menerapkan pola asuh otoriter pada anak-anaknya dalam bentuk kekerasan verbal (yang berupa bentakan dan labeling pada anak), membatasi anak untuk bertanya, peraturan-peraturan kaku yang dibuat sepihak oleh orang tua, komunikasi yang cenderung satu arah dan ketidaksabaran orang tua saat mendampingi anak mengaji dan hafalan yang berujung pada kemarahan orang tua. Berbagai faktor yang melatarbelakangi munculnya pengasuhan otoriter antara lain, (1) pola asuh orang tua yang didapat dari orang tua sebelumnya (2) metode penanaman keagamaan yang kurang tepat (3) Tuntutan sekolah yang berbasis agama, (4) Persaingan antar orang tua.